Persepsi Orang Tua terhadap Pembelajaran Daring Pendidikan Jasmani di Sekolah Dasar - Muhammad Haris Faza; Lulu April Farida (Universitas Negeri Semarang, 2023)
The purpose of this study is to find out how parents perceive online physical education learning at Al Madina Islamic Elementary School for the 2020/2021 Academic Year. This research method is Qualitative Etnography. The subjects of this study were parents of 30 students. Data collection techniques using questionnaires and documentation. This results of this study indicate that the average student’s parents have the perception that physical education online learning causes a decrease in students’ enthusiasm for learning, causing students to only get grades or learning outcomes and mastery of the material is less than optimal. Parents assume that the practical learning process is also less than optimal due to the lack of tools used as media for childrens’s practice at home and the absence of supervision from the teacher so that children or students do not know what is being done is right or wrong. The conclusion of this study is that parents have the perception that online learning of physical education causes a decrese in students’ enthusiasm for learning. Then parents assume that the teacher only focuses on providing materials and in practice there is no supervision from the teacher and the rest is left to parents and students.